Analysis of sustainable polyester tiles of domestic waste - Igwe, Isaac Ogbennaya; Oragwu, Ifeoma Perpetua; Nwapa, Chinedu (Penerbit Universiti Kebangsaan Malaysia, 2024)
Sustainable unsaturated polyester resin composite tiles were prepared using snail shell powder by open mould technique. The snail shell powder filler was obtained from snail shell, a domestic waste. The filler characterized for pH (7.61), bulk density (1.33), specific gravity (1.80 g/cm3 ), refractive index (1.45), oil absorption (5.0 g/100 g), and moisture content (14.01%) was incorporated into the polymer matrix at 0 to 30 wt. % filler content. The tensile, and compressive strength of the tile samples decreased with filler content whereas the impact, hardness, and specific gravity increased with filler content, and were generally greater than those of cured unsaturated polyester resin at any filler content considered. The tile samples containing 15, and 25 wt. % snail shell powder were vitreous while the samples containing 10, 20, and 30 wt.% snail shell powder were semi – vitreous. The low water absorption property of the tile samples makes them suitable for household utilizations in areas such as kitchen walls, floors, backlashes, and shower walls, and should justify the use of low - cost snail shell powder in the composite industry. This will lead to a cost - effective handling and management of snail shell waste thereby, providing a clean environment.